Tooth embedding medium influences the accuracy of electronic apex locator - Guerreiro-Tanomaru, Juliane M; Croti, Hugo R; Silva, Guilherme F; Faria, Gisele [UNESP]; Tanomaru-Filho, Mário (My University, 2012)
This study evaluated the influence of tooth embedding media on the accuracy ofan electronic apex locator. The root canal length of 20 human mandibular canines was measured by inserting a 15 K-file into the root canal up to the apical foramen. The distance was measured with a digital caliper. The embedding media evaluated were alginate, saline, floral foam or gauze soaked in saline. Electronic root canal length measurement was performed with Root ZX II. Data were analysed using ANOVA for repeated measurements and Tukey test, at a significance level of 5%. There was no difference between the actual root canal length measurement and the electronic reading recorded with alginate medium. The readings obtained with the other media differed from the actual root canal length measurements. Alginate provided greater accuracy in electronic root canal length determination by Root ZX II than saline, floral foam and gauze.
Keywords: endodontics; histology; human; reproducibility; tooth root; Humans; Reproducibility of Results; Root Canal Preparation; Tooth Apex